Student Misbehaviour in Classrooms at Secondary Schools and the Relationship with Teacher Job Well-Being - Sidek, Zalifah; Surat , Shahlan; Kutty, Faridah Mydin (International Journal of Psychosocial Rehabilitation, 2020)
A healthy and enjoyable classroom environment affects the students’ positive development of learning as well as enhances the teacher’s enthusiasm for teaching. But this decade, the challenge of discipline and student misbehavior in the classroom has affected the well-being of teachers which led to disruptive emotions and influenced the effectiveness and enjoyableness of learning experience among students. The study was conducted to identify the level of student misbehavior, the level of job well-being and to identify the relationship between student misbehavior and the well-being of teachers. The study sample consisted of 460 secondary school teachers in the Klang Valley Malaysia using a proportional stratified random sampling. The research used quantitative survey method by distributing questionnaire to teachers from 30 schools involved in this study. This study used descriptive and Pearson correlation inferential analysis. The findings showed that the stress from student misbehavior in the classroom and the well-being of teachers are at a moderately low level. Correlation analysis found that student misbehavior was significantly associated with teacher job well-being, which was positively related to job satisfaction but was not associated with emotional exhaustion.